2015
DOI: 10.1620/tjem.235.267
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Exon 4 in the N-Acetylgalactosamine-4-Sulfatase Gene in a Taiwanese Patient with Mucopolysaccharidosis Type VI

Abstract: Mucopolysaccharidosis type VI (MPS VI) is a rare autosomal recessive disorder caused by a deficiency of N-acetylgalactosamine-4-sulfatase (ARSB), one of the enzymes required for the degradation of dermatan sulfate (DS). Accumulation of DS in connective tissue causes growth failure, resulting in short stature. Here, we observed a 5-year-old girl who was the only one affected member of her family and who presented with an exaggerated, convex curvature of the back at the age of one year. Abnormal excretion of DS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…c.1072G/A (p.V358M) and c.1191A/G (p.P397P) polymorphisms were detected earlier in MPS VI patients in Taiwan. Although the prevalence of MPS VI is lower (three patients diagnosed with MPS VI in 11 years; one in 875,000 newborns), the variety of mutations is much greater in Taiwan [ 126 , 127 , 128 , 129 ]. Research conducted in Brazil indicated that the p.H178L missense mutation had a founder effect on Brazilian MPS VI patients.…”
Section: Mutationsmentioning
confidence: 99%
“…c.1072G/A (p.V358M) and c.1191A/G (p.P397P) polymorphisms were detected earlier in MPS VI patients in Taiwan. Although the prevalence of MPS VI is lower (three patients diagnosed with MPS VI in 11 years; one in 875,000 newborns), the variety of mutations is much greater in Taiwan [ 126 , 127 , 128 , 129 ]. Research conducted in Brazil indicated that the p.H178L missense mutation had a founder effect on Brazilian MPS VI patients.…”
Section: Mutationsmentioning
confidence: 99%
“…CNVs in MPS-related genes have been characterized and encompass: (i) deletion of exon 14-3′UTR, and duplication of exon 2-intron 12 in IDUA in patients affected by MPS I [ 42 , 43 ]; (ii) deletion of SGSH exons 1–5 in MPS IIIA patients [ 44 ]; (iii) Alu -mediated deletion of NAGLU exons 3–4 in patients with MPS IIIB/Sanfilippo type B syndrome [ 45 , 46 ]; (iv) heterozygous deletion of exon 15 [ 47 ] and homozygous deletion of exons 9–10 in HGSNAT in MPS IIIC or Sanfilippo type C patients [ 43 ]; (v) deletions of GNS exon 1, 2–3, 6–7, 9–14 in patients affected by MPS IIID/Sanfilippo disease type D [ 48 , 49 ]; (vi) deletion of multiple contiguous exons including 1–3, 2–4, 2–5, 3–14, 5–8, 9–14, 10–14, 11–12, and single exon 5 and 13 of GALNS in patients with MPS IVA/Morquio A [ 43 , 50 , 51 , 52 , 53 ]; (vii) ARSB deletion of exons 2–3, exon 4 and exon 5 MPS VI patients [ 54 , 55 , 56 ].…”
Section: Svs In Lsdsmentioning
confidence: 99%
“…A deletion of exon 4 [c.(690+1_691‐1)_(898+1_899‐1)del; breakpoints unknown] in its entirety was reported in homozygosity in one female Taiwanese individual. This deletion is expected to result in frameshift, premature truncation, and loss of significant portions of the catalytic domain (Lin, Ke, Chou, Wang, & Tsai, ). Finally, a genomic deletion of exon 5 [c.(898+1_899‐1)_(1142+1_1143‐1)del] was reported eight times, once in homozygosity in a male Italian individual, who displayed a classical, severe MPS VI phenotype (Ferla et al., ).…”
Section: Variantsmentioning
confidence: 99%